The EU law terminology: between the identity of translator and that of recipient - Ciostek, Anna (Traduttologia e Traduzioni, vol. II: Identità linguistica - identità culturale, 2021)
The EU law terminology has enriched Polish legal language since Poland’s accession to the EU and has been subject to changes. Apart from the terms borrowed from English and French, there are more and more polonized equivalents, closer to the linguistic identity of their recipients. At the same time, in the general language, we observe the creation of equivalents of these terms in other registers. They are calles bruxelisms, which are evolving and being terminologized.